The Relationship Between Religiosity and Sexual Behavior in Adolescents in Merdeka Square, Langsa City - Alfita, Laili; Ulfa, Tisna Catur; Ghalda, Inas (Universitas Muhammadiyah Yogyakarta, 2021)
This study aims to determine the relationship between religiosity and sexual behavior in dating adolescents in Merdeka Square, Langsa City. The research focuses on the relationship between religiosity and sexual behavior. The method used in this research was the quantitative correlation method. The research sample was teenagers dating in Merdeka Square, Langsa City, as many as 40 couples aged 17-21 years. The scale employed was a Likert scale model and the semantic differential. The sampling technique used accidental sampling. Data analysis employed the Product Moment correlation method from Karl Pearson. The study results revealed a significant relationship between religiosity and sexual behavior. The reliability of the religiosity scale rbt = 0.898, and the reliability of the sexual behavior scale rbt = 0.968. The data analysis technique used was the Product Moment correlation technique, utilizing SPSS version 18.0. Based on data analysis, it was found that a significant positive relationship between religiosity and sexual behavior in dating adolescents in Merdeka Square, Langsa City. It was indicated by the coefficient rxy = 0.401 with p (0.000) < 0.010. The hypothetical results obtained from this study are that religiosity was classified as low with a hypothetical mean value of 80 and an empirical mean value of 93.19, while sexual behavior was classified as high with a hypothetical mean value of 136 and an empirical mean value of 139.79. From the results of this study, religiosity contributes to sexual behavior by 16.1%, so that the proposed hypothesis was accepted.